2011
DOI: 10.1080/00918369.2011.605736
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Multiple Identities: How African-American Gay and Bisexual Men Persist at a Predominantly White Institution

Abstract: This consensual qualitative research (CQR) study explores factors contributing to the persistence of African-American gay and bisexual men at a predominately White institution (PWI). Eight participants consistently noted that involvement with an African-American community was crucial to navigating the challenges of attending a PWI. Participants reported that their racial identity was more salient than their sexual orientation in creating social support, and they described feeling uncomfortable using lesbian, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 1 publication
3
32
0
Order By: Relevance
“…An especially salient element in participants' stories was the reaction of other Black students to them based on heterosexist, religiocultural expectations of what it means to be a Black man, specifically with regard to gender presentation and sexuality (Patton, 2011). Participants in several studies found ways to survive in settings that were physically and psychologically hostile due to racialized heterosexism and homophobia (Goode-Cross & Good, 2008Goode-Cross & Tager, 2011;Gresham, 2009;McCready, 2004;Patton, 2011;Vaught, 2004;Washington & Wall, 2006). Many participants reported creating supportive "safe spaces" where they could be themselves (Goode-Cross & Good, 2008).…”
Section: Socialization Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…An especially salient element in participants' stories was the reaction of other Black students to them based on heterosexist, religiocultural expectations of what it means to be a Black man, specifically with regard to gender presentation and sexuality (Patton, 2011). Participants in several studies found ways to survive in settings that were physically and psychologically hostile due to racialized heterosexism and homophobia (Goode-Cross & Good, 2008Goode-Cross & Tager, 2011;Gresham, 2009;McCready, 2004;Patton, 2011;Vaught, 2004;Washington & Wall, 2006). Many participants reported creating supportive "safe spaces" where they could be themselves (Goode-Cross & Good, 2008).…”
Section: Socialization Factorsmentioning
confidence: 94%
“…Many participants reported creating supportive "safe spaces" where they could be themselves (Goode-Cross & Good, 2008). Participants also reported using other coping strategies such as selective disclosure (Goode-Cross & Good, 2008Patton, 2011), compartmentalization of their multiple identities (Gresham, 2009), maintenance of superficial relationships with other Blacks (Washington & Wall), or avoiding gay male students or Black students (Goode- Cross & Good, 2009;Goode-Cross & Tager, 2011).…”
Section: Socialization Factorsmentioning
confidence: 94%
“…Men of color of the AIDS-2 Generation are far better represented in empirical research compared to prior generations. The consistent theme of challenge with regard to integrating racial and sexual identities emerges from studies of men of color of this generation (e.g., Bowleg, 2013; Christian, 2005; Goode-Cross & Tager, 2011; Hunter, 2010), as does the theme of experiencing ethnic minority stress in the gay community but sexual minority stress in the ethnic minority community (e.g., Hidalgo, Cotten, Johnson, Kuhns, & Garafalo, 2013). The phenomenon of ethnic minority men (typically African American and Latino) rejecting gay identity labels and identification with the gay community but engaging in same-sex practices is particularly well documented for men of this generation (e.g., Dodge, Jeffries, & Sandfort, 2008; Martinez & Hosek, 2005).…”
Section: Five Generations Of Gay Men In the Usmentioning
confidence: 98%
“…A number of examples (Blackburn, ; Goode‐Cross & Tager, ; Harper & Gasman, ; Harris, ; McCready, ; Patton, ; Strayhorn, Blakewood, & DeVita, ; Vaught, ) speak to the focus on Black queer males. While more scholarship is needed on Black queer males, the extant literature offers more on their experiences than Black queer females (Blackburn, ; Patton & Simmons, ; Quinn, ), queer Latinos (Cruz, ; Misa, ), queer Asians (Ngo, ; Varney, ), and trans students of color (Brockenbrough & Boatwright, Forthcoming).…”
mentioning
confidence: 99%